2018
DOI: 10.1007/s10519-018-9922-2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Repeated Treatment with Midazolam in SHR and SLA16 Rat Strains in the Triple Test

Abstract: We exposed male and female rats of SHR (Spontaneously Hypertensive Rats) and SLA16 (SHR.LEW-Anxrr16) strains, in a non-drugged state, for five consecutive days to the Triple Test (experiment 1); or after repeated treatment with midazolam (MDZ), for four consecutive days. The fifth day was performed without treatment (experiment 2). The first experiment showed that males did not avoid and females increased the exploration of the open arms over the days. In experiment 2, SLA16 from both sexes approached more the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 55 publications
1
0
0
Order By: Relevance
“…In another study, SHR and SLA16 rats were submitted to the triple test (an apparatus combining the OF, EPM and BWB) for five consecutive days, after repeated treatment with midazolam. It was shown that SLA16 females increased exploration of the open arms of the EPM over days, corroborating the notion that Anxrr16 influences anxiety-like behaviors related to novelty [ 68 ].…”
Section: The Sla16 Congenic Strainsupporting
confidence: 64%
“…In another study, SHR and SLA16 rats were submitted to the triple test (an apparatus combining the OF, EPM and BWB) for five consecutive days, after repeated treatment with midazolam. It was shown that SLA16 females increased exploration of the open arms of the EPM over days, corroborating the notion that Anxrr16 influences anxiety-like behaviors related to novelty [ 68 ].…”
Section: The Sla16 Congenic Strainsupporting
confidence: 64%